P21-Activated Kinase 4 Pak4 Maintains Embryonic Stem Cell Pluripotency via Akt Activation - Cheng, Fangyuan; Li, Mingyue; Thorne, Rick Francis; Liu, Guangzhi; Zhang, Yuwei; Wu, Mian; Liu, Lianxin (Stem cells (Dayton, Ohio), 2022)
Exploiting the pluripotent properties of embryonic stem cells (ESCs) holds great promise for regenerative medicine. Nevertheless, directing ESC differentiation into specialized cell lineages requires intricate control governed by both intrinsic and extrinsic factors along with the actions of specific signaling networks. Here, we reveal the involvement of the p21-activated kinase 4 (Pak4), a serine/threonine kinase, in sustaining murine ESC (mESC) pluripotency. Pak4 is highly expressed in R1 ESC cells compared with embryonic fibroblast cells and its expression is progressively decreased during differentiation. Manipulations using knockdown and overexpression demonstrated a positive relationship between Pak4 expression and the clonogenic potential of mESCs. Moreover, ectopic Pak4 expression increases reprogramming efficiency of Oct4-Klf4-Sox2-Myc-induced pluripotent stem cells (iPSCs) whereas Pak4-knockdown iPSCs were largely incapable of generating teratomas containing mesodermal, ectodermal and endodermal tissues, indicative of a failure in differentiation. We further establish that Pak4 expression in mESCs is transcriptionally driven by the core pluripotency factor Nanog which recognizes specific binding motifs in the Pak4 proximal promoter region. In turn, the increased levels of Pak4 in mESCs fundamentally act as an upstream activator of the Akt pathway. Pak4 directly binds to and phosphorylates Akt at Ser473 with the resulting Akt activation shown to attenuate downstream GSK3β signaling. Thus, our findings indicate that the Nanog-Pak4-Akt signaling axis is essential for maintaining mESC self-renewal potential with further importance shown during somatic cell reprogramming where Pak4 appears indispensable for multi-lineage specification.Exploiting the pluripotent properties of embryonic stem cells (ESCs) holds great promise for regenerative medicine. Nevertheless, directing ESC differentiation into specialized cell lineages requires intricate control governed by both intrinsic and extrinsic factors along with the actions of specific signaling networks. Here, we reveal the involvement of the p21-activated kinase 4 (Pak4), a serine/threonine kinase, in sustaining murine ESC (mESC) pluripotency. Pak4 is highly expressed in R1 ESC cells compared with embryonic fibroblast cells and its expression is progressively decreased during differentiation. Manipulations using knockdown and overexpression demonstrated a positive relationship between Pak4 expression and the clonogenic potential of mESCs. Moreover, ectopic Pak4 expression increases reprogramming efficiency of Oct4-Klf4-Sox2-Myc-induced pluripotent stem cells (iPSCs) whereas Pak4-knockdown iPSCs were largely incapable of generating teratomas containing mesodermal, ectodermal and endodermal tissues, indicative of a failure in differentiation. We further establish that Pak4 expression in mESCs is transcriptionally driven by the core pluripotency factor Nanog which recognizes specific binding motifs in the Pak4 proximal promoter region. In turn, the increased levels of Pak4 in mESCs fundamentally act as an upstream activator of the Akt pathway. Pak4 directly binds to and phosphorylates Akt at Ser473 with the resulting Akt activation shown to attenuate downstream GSK3β signaling. Thus, our findings indicate that the Nanog-Pak4-Akt signaling axis is essential for maintaining mESC self-renewal potential with further importance shown during somatic cell reprogramming where Pak4 appears indispensable for multi-lineage specification.